SIGNIFIKANSI DAN IMPLIKASI PERBEDAAN SPESIFIKASI RETURN DALAM PENELITIAN PASAR MODAL - WIRAMA, DEWA GEDE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009))
The purpose of this research is to determine the statisticalsignificance and implication of various specifications of stock return.Three specifications are considered, i.e. return that (1) ignoresdividend, (2) ignores the proceed from further investment ofdividend, and (3) assumes that dividend is reinvested in the samestock. The differences among the three specifications are analyzedunder one, four, and seven years of investment periods.Using a sample consisted of 102 companies listed on theIndonesian Stock Market during the seven year period starting fromthe beginning of 2001, it is found that each return specificationresults in return numbers that in general are statistically differentfrom each other. The only insignificant difference is the differencebetween return that ignores proceed from further investment ondividend and the one that assumes that dividend is reinvested in thesame stock for one year of investment in stock.The implication of the differences in returns calculated undereach specification is further analyzed using an association studythat regresses market return on accounting return (ROE) in the sameone, four, and seven year periods of investment. Each returnspecification produces different R2s and betas. Statisticallysignificant differences are found in the analysis with four and sevenyear periods of investment, except for the difference between returnsthat, again, ignores the proceed from further investment on dividendand the one that assumes that dividend is reinvested in the samestock for seven years of investment in stock.The conclusion of this research is that ignoring dividend inreturn calculation might lead to inaccurate results. The impact ofignoring further investment of dividend is somewhat less severethan the impact of ignoring dividend altogether.
Keywords: return specification, dividend, reinvestment, statistical difference